Experimental identification of I-mode characteristics at the edge of FIRE mode in KSTAR - Chweeho Heo; SangJin Park; GyungJin Choi; Jaewook Kim; Eun-jin Kim; YoungMu Jeon; Minjun J. Choi; Hyunsun Han; Choongki Sung; TaikSoo Hahm; Yong-Su Na (Nuclear Fusion)
The edge region of the recently discovered fast ion-regulated enhancement mode (FIRE mode) (Han and Park et al 2022 Nature 609 269–275), which primarily operates in the unfavorable ion $\nabla B$ drift configuration, is investigated in detail for the first time. An ion temperature pedestal is identified, while the edge electron density profile remains at low-confinement mode (L-mode) level, displaying characteristics of the edge profiles in improved energy confinement mode (I-mode). The weakly coherent mode (WCM) is observed at around 50 kHz in the spectrum of edge electron density fluctuations measured by beam emission spectroscopy. The weakly coherent feature becomes more pronounced as the amplitude of intermediate-frequency fluctuations (approximately 10–30 kHz) decreases, coinciding with a rise in the height of the temperature pedestal. The WCM propagates in the ion diamagnetic drift direction in the laboratory frame, but its propagation direction in the E × B flow frame has yet to be determined. Nonlinear phase coupling between the low-frequency density fluctuation components and the WCMs is identified, indicating the presence of zonal density. This coupling typically occurs as the H-mode transition approaches, and its potential link to a regulatory process is discussed. When the coupling manifests, intermittent bursts are observed concurrently, not just at the radial location where the WCM amplitude peaks, but throughout the edge region. No other coherent oscillations with finite frequency have been detected thus far.